2020
DOI: 10.3389/fimmu.2020.565746
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Social Housing Changes on Immunity and Vaccine-Specific Immune Responses in Adolescent Male Rhesus Macaques

Abstract: Nonhuman primates (NHPs) in research institutions may be housed in a variety of social settings, such as group housing, pair housing or single housing based on the needs of studies. Furthermore, housing may change over the course of studies. The effects of housing and changes in housing on cell activation and vaccine mediated immune responses are not well documented. We hypothesized that animals moved indoors from group to single housing (GH-SH) would experience more stress than those separated from groups int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…We acknowledge that this is a significant limitation of this study given that the complexity of social interactions in macaques can sometimes lead to individuals who experience greater stress from their social status than they would without contact with conspecifics ( 54 57 ). However, numerous publications have demonstrated the overall positive impact of social housing in comparison to single housing in diverse populations of macaques as assessed by both behavioral outcomes and immune function ( 53 , 58 60 ). One of these positive impacts is the phenomenon of social buffering.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We acknowledge that this is a significant limitation of this study given that the complexity of social interactions in macaques can sometimes lead to individuals who experience greater stress from their social status than they would without contact with conspecifics ( 54 57 ). However, numerous publications have demonstrated the overall positive impact of social housing in comparison to single housing in diverse populations of macaques as assessed by both behavioral outcomes and immune function ( 53 , 58 60 ). One of these positive impacts is the phenomenon of social buffering.…”
Section: Discussionmentioning
confidence: 99%
“…Macaques are naturally social animals that require interaction with conspecifics to maintain their psychological welfare (49,50). This trait makes them a natural model to recapitulate psychosocial stress in a controlled setting, and multiple experimental designs have been used to validate the physiological and behavioral changes that occur in macaques under different social conditions (29,(51)(52)(53). Because this was a retrospective investigation, no stress biomarkers or behavioral assessments are available for the animals in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In the opinion of these research teams, pair- and group-housed animals are more content, calmer, and may recover more quickly from procedures than singly housed animals on studies involving high containment pathogens. Social buffering studies (including in BSL-2) have shown the powerful role of social housing in mitigating reactions of NHPs to stressful events, enhancing immune responses, and optimizing the ability to cope with disease, potentially leading to models that are more representative of the human condition [ 13 , 40 , 41 , 42 , 43 , 44 , 45 ]. It is conceivable that working with calmer, less stressed subjects could also result in less variable data and more reproducible findings, which may enable a reduction in NHP use, though to our knowledge, this has not yet been proven in specifically designed studies.…”
Section: Refinement Opportunitiesmentioning
confidence: 99%
“…Interestingly, both stereotypic behaviors and SIB were associated with physiological consequences, including suggested malfunction of neurological loops connecting the cortex and the basal ganglia (Pomerantz et al, 2012), altered dopamine receptor levels in various brain regions (Freeman et al, 2015), and altered serotonin and opioid measures, in addition to changing responses to stress (see Tiefenbacher et al, 2005 for a review). The variation introduced by social housing conditions may be also be manifested in by additional outcome measures, including urinary cortisol (Hannibal et al, 2018), fecal cortisol and heart rate (Doyle et al, 2008), proliferating B cells (Pahar et al, 2020), neuroendocrine function (e.g., see review by Cacioppo et al, 2015), and the ratio of CD4 to CD8 lymphocytes (Schapiro et al, 2000). Furthermore, several serum biochemical and hematological parameters, such as blood urea nitrogen, glucose, alanine aminotransferase, and serum calcium concentrations, differed significantly between singly housed and socially housed cynomolgus macaques ( Macaca fascicularis ) (Koyama et al, 2018; Xie et al, 2014).…”
mentioning
confidence: 99%